1995
DOI: 10.1007/bf02032574
|View full text |Cite
|
Sign up to set email alerts
|

Release of cytokines from isolated lung strips by bradykinin

Abstract: Bradykinin as an inflammatory mediator was assayed for its ability to release cytokines from isolated lung tissue derived from guinea pigs, mice and in some cases from patients. Bradykinin elicited in concentrations, which were able to induce a contraction of isolated lung strips, a secretion of different cytokines from the tissue into organ baths as well as from lung tissue incubated in petri dishes (4h, 37 degrees C). Using enzyme immuno assays and the tanned erythrocyte electrophoretic mobility (TEEM)-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…However, little is known about the role of BK in regulating cytokine gene expression. A recent study demonstrated that BK stimulates the synthesis of IL-1␤, IL-2, and IL-6 from lung strip explants, an effect susceptible to blockade by a B2 BK receptor antagonist (31). Results presented in this report provide the first evidence that BK can stimulate cytokine gene expression through activation of the transcription factor NF-B, a potentially important mechanism for the inflammatory effects of kinins.…”
Section: Discussionmentioning
confidence: 52%
“…However, little is known about the role of BK in regulating cytokine gene expression. A recent study demonstrated that BK stimulates the synthesis of IL-1␤, IL-2, and IL-6 from lung strip explants, an effect susceptible to blockade by a B2 BK receptor antagonist (31). Results presented in this report provide the first evidence that BK can stimulate cytokine gene expression through activation of the transcription factor NF-B, a potentially important mechanism for the inflammatory effects of kinins.…”
Section: Discussionmentioning
confidence: 52%
“…Bradykinin, kallidin, des-Arg 9 -bradykinin, des-Arg 10 -kallidin, NFormyl-Met-Leu-Phe (FMLP), leukotriene B 4 (LTB 4 …”
Section: Methodsmentioning
confidence: 99%
“…Paegelow/Trzeczak/Böckmann/Vietinghoff Additionally, kinins have themselves the capacity to induce the release or formation of further inflammatory mediators, for instance cytokines, prostaglandins and leukotrienes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that BK stimulated human lung fibroblasts to produce interleukin (IL)-8 by increasing its gene expression [11]. BK also increases the production of IL-1, IL-2, and IL-6 from isolated guinea pig lung strips [12], and IL-1 from cultured human lung fibroblasts [13]. These data suggest that BK may be involved in the control of the inflammatory reaction associated with interstitial lung disorders through proinflammatory cytokines production by lung fibroblasts.…”
mentioning
confidence: 99%